Olig2+/NG2+/BLBP+ astrocyte progenitors: a novel component of the neurovascular unit in the developing mouse hippocampus - Omura, Shoichiro; Ogawa, Rina; Kawachi, Tomomi; Ogawa, Aya; Arai, Yuuki; Takayama, Natsumi; Masui, Aki; Kondo, Kumiko; Sugimoto, Hiroki; Shinohara, Hiroshi M.; Takahashi, Tokiharu; Maeda, Hideyuki; et al. (Frontiers in Cellular Neuroscience, 2024)
Astrocytes are key components of the neurovascular unit. While we have recently identified Olig2+ astrocyte progenitors (ASPs) in the developing mouse dentate gyrus (DG), their molecular signature remains incompletely characterized. Here we demonstrate that Olig2+ ASPs predominantly express brain lipid-binding protein (BLBP), while only a small population of them expresses gfap-GFP. These Olig2+/BLBP+ ASPs co-express the transcription factors Sox3, Sox9 and the proteoglycan NG2 but not Sox10, a marker for oligodendrocyte progenitors (OLPs).Olig2+ ASPs appear from embryonic day 18 (E18) onwards and decline at postnatal day 14 (P14).Consistent with the proliferation of both Olig2+ and NG2+ glial cells after brain injury, intrauterine intermittent hypoxia (IH) led to an increase in Olig2+/NG2+/BLBP+ ASPs in the postnatal DG. IH also promoted both angiogenesis and vascular coupling of Olig2+/NG2+ ASPs.Our data suggest that IH-induced expression of HIF1a increases Olig2+/NG2+/BLBP+ ASPs in a cell non-autonomous manner. Our data also revealed increased vascular coupling of GFAP+ astrocytes following IH, while the number of GFAP+ astrocytes remains unchanged. Given that BLBP, Olig2 and NG2 are expressed in reactive astrocytes, our findings suggest that Olig2+/NG2+/BLBP+ ASPs represent a subtype of reactive astrocyte progenitors. Furthermore, the enhanced vascular coupling of Olig2+/NG2+/BLBP+ ASPs appears to be an adaptive response to hypoxic brain injury. This study provides new insights into the molecular characteristics of Olig2+/NG2+/BLBP+ ASPs and their potential role in the brain's response to hypoxic injury, contributing to our understanding of neurovascular unit dynamics in both development and pathological conditions.